Human and Vehicle Factor on Traffic Accidents in The City of Makassar in 2019-2021 - Mallapiang, Fatmawaty; Al Mukarramah, Al Mukarramah; Sadarang, Rimawati Aulia Insani; Nurhidayat, Nurhidayat (Public Health Science & Religion, 2024)
Background: Traffic accidents are a public health problem that affects all sectors of life. The purpose of this study is to describe the human and vehicle factors for traffic accidents in Makassar City in 2019-2021. Methods. This research is a descriptive quantitative research with a secondary data analysis (ADS) approach. Results. The highest accident factor was caused by the human factor as much as 96.48%. The perpetrators of traffic accidents were mostly male as much as 70.9% and the victims were female as much as 53.9%. Perpetrators aged 16-20 years were 39.1% and victims aged over 51 years were 22.2%. Based on the highest level of education, it occurs at the high school level, with 66.6% of perpetrators and 42.5% of victims. victim. disorderly behavior of 90.2% which is the cause of accidents based on the human factor. Meanwhile, the vehicle factor is 1.07%. Every driver must comply with the applicable traffic regulations as a necessity in order to arrive safely at their destination. Conclusion. Penyebab kecelakaan lalu lintas di Kota Makassar dari tahun 2019 sampai dengan tahun 2021, terdapat 96,48% faktor manusia (human error). Kecelakaan lalu lintas berjenis kelamin laki-laki sebanyak 70,9%